A dimensão ético-política da crítica platônica à mímesis na Politéia - Jovelina Maria Ramos de Souza (2003)
From the initial reading of Platos Politeia we turn to Homers Iliad and Odyssey aiming at understanding the political and ethical dimensions of Platos criticisms to poetry. In our approach to this question we try to understand, on one hand, the significance of Homers poetry for the education of the Greeks and, on the other, the different meanings mimesis acquires in the Politeia, to finally move on to analyze Plato's attack. In this quarrel, two claims to knowledge are confronted, poetry and philosophy, akin and opposite to each other, which Plato seeks to articulate in his project of producing a city with words. Plato's criticism to poetry is, above all, part of a radical project of educating citizens for the just exercise of power, a project which is grounded on the dialectical search for what the human soul and city can and must be.